2006
DOI: 10.1016/j.jcat.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Growth and structural stability of well-ordered PdZn alloy nanoparticles

Abstract: Despite many recent attempts to unravel the structure of novel PdZn alloys, promising catalysts in methanol steam reforming, a detailed study on the formation of Pd-Zn alloy particles and of their structural and thermal stability is still missing. We take advantage of the unique properties of epitaxially grown Pd particles embedded in layers of amorphous ZnO and mechanically stabilized by SiO 2 , and present an electron microscopy study of the preparation of well-ordered PdZn alloy nanoparticles at surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 32 publications
5
43
0
3
Order By: Relevance
“…In practice, it has been shown that a transition from metal particles, which consist of one component that is in contact with an oxidic support, toward supported bimetallic phases can be induced by pre-treatment with a reductive catalyst. [1,[31][32][33][34][35][36][37][38][39][40][41][42] In specific cases (e.g. PdÀZn catalysts), even a highly ordered bimetallic compound can be formed by reduction in H 2 , which may be a necessary prerequisite for the most selective and active state of the respective catalyst.…”
Section: And Comentioning
confidence: 99%
“…In practice, it has been shown that a transition from metal particles, which consist of one component that is in contact with an oxidic support, toward supported bimetallic phases can be induced by pre-treatment with a reductive catalyst. [1,[31][32][33][34][35][36][37][38][39][40][41][42] In specific cases (e.g. PdÀZn catalysts), even a highly ordered bimetallic compound can be formed by reduction in H 2 , which may be a necessary prerequisite for the most selective and active state of the respective catalyst.…”
Section: And Comentioning
confidence: 99%
“…Apart from advanced copper-based catalysts, [1,2] special attention is presently paid to the highly MSR-selective reduced state of Pd/ZnO, [3] containing a particularily stable intermetallic PdZn (1:1) active phase. [3,4] Therefore, we recently studied related "inverse" near-surface PdZn intermetallic phases, showing that three-dimensional PdZn active site ensembles are equally important for selective dehydrogenation of methanol (thus avoiding CO) and for efficient water activation. [5] For the less costly Cu/ZnO catalysts, originally designed for methanol synthesis, improvements towards a technical MSR application regarding sintering stability, pyrophoricity, and selectivity are still required.…”
mentioning
confidence: 99%
“…Um die technischen Probleme und Risiken zu vermeiden, die mit der Benutzung, Lagerung und dem Transport von Wasserstoff verbunden sind, bietet sich Methanol als praktischer und verfügbarer Energieträger für die Bereitstellung von H 2 an. [3,4] Aus diesem Grund haben wir kürzlich "inverse" oberflächennahe intermetallische PdZn-Phasen studiert und gezeigt, dass dreidimensionale aktive/selektive PdZn-Ensembles sowohl die selektive Dehydrierung von Methanol steuern (wodurch die Produktion von CO verhindert wird) als auch eine effektive Wasseraktivierung bewirken. Wasserstoff kann durch die katalytische Methanoldampfreformierung (MSR) aus Methanol erzeugt werden: CH 3 OH + H 2 O!CO 2 + 3 H 2 .…”
unclassified
“…hat aktuell auch der hoch MSRaktive reduzierte Zustand von Pd/ZnO, [3] mit einer speziell stabilen intermetallischen 1:1-PdZn-Phase, Aufmerksamkeit erregt. [3,4] Aus diesem Grund haben wir kürzlich "inverse" oberflächennahe intermetallische PdZn-Phasen studiert und gezeigt, dass dreidimensionale aktive/selektive PdZn-Ensembles sowohl die selektive Dehydrierung von Methanol steuern (wodurch die Produktion von CO verhindert wird) als auch eine effektive Wasseraktivierung bewirken. [5] Die billigeren Cu/ZnO-Katalysatoren, ursprünglich für die Metha-nolsynthese entwickelt, bedürfen noch einiger Verbesserungen in Bezug auf Sinterstabilität, Selbstentzündung und Selektivität, um für die technische Reformieranwendung geeignet zu sein.…”
unclassified